2016
DOI: 10.1007/s12035-016-9920-4
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoprotein D Overexpression Protects Against Kainate-Induced Neurotoxicity in Mice

Abstract: Excitotoxicity due to the excessive activation of glutamatergic receptors leads to neuronal dysfunction and death. Excitotoxicity has been implicated in the pathogenesis of a myriad of neurodegenerative diseases with distinct etiologies such as Alzheimer's and Parkinson's. Numerous studies link apolipoprotein D (apoD), a secreted glycoprotein highly expressed in the central nervous system (CNS), to maintain and protect neurons in various mouse models of acute stress and neurodegeneration. Here, we used a mouse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 96 publications
1
15
0
Order By: Relevance
“…Among the 75 candidate genes shown in Figures 3 A and 3B, S100A6 , 15 FosB , 16 ARHGDIB , 17 SOD3 , 18 and ApoD 19 have been previously implicated in promoting cell survival. Further RT-PCR validation showed that only the top-ranked S100A6 showed corresponding induction in BCs in response to exosome treatment ( Figure 3 C).…”
Section: Introductionmentioning
confidence: 99%
“…Among the 75 candidate genes shown in Figures 3 A and 3B, S100A6 , 15 FosB , 16 ARHGDIB , 17 SOD3 , 18 and ApoD 19 have been previously implicated in promoting cell survival. Further RT-PCR validation showed that only the top-ranked S100A6 showed corresponding induction in BCs in response to exosome treatment ( Figure 3 C).…”
Section: Introductionmentioning
confidence: 99%
“…One possible interpretation is that ApoD could also participate in the elimination of harmful waste products (oxidized lipids) and pro-inflammatory molecules (ARA) from the CNS or other targeted tissues. ApoD is overexpressed in periods of neurodegenerative stress [15,[50][51][52][53][54][55]. ApoD is known to facilitate myelin clearance, extracellular matrix remodeling and axon regeneration after nerve injury [17].…”
Section: Discussionmentioning
confidence: 99%
“…ApoD can also limit inflammation and oxidative stress by reducing oxidized lipids [1,[9][10][11][12]. Because it is overexpressed during many neurodegenerative diseases and stresses, ApoD is considered an important factor in brain protection and repair [9,11,[13][14][15]. ApoD is also a member of the apolipoprotein family as it associates with lipoproteins (mainly high-density lipoproteins) in the blood.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Najyb et al (2017) demonstrated that hApo D internalization and accumulation in primary hippocampal neurons were accentuated by kainate treatment. In addition, these authors reported that hApo D could act by decreasing abnormally increased cholesterol levels in damaged neurons [ 68 ]. In this line, He et al (2009) showed that hApo D purified from BCF was able to bind arachidonic acid and cholesterol, attenuating the increase in oxidants and proinflammatory derivatives as F(2)-isoprostanes and 7-ketocholesterol in similar pathological conditions [ 69 ].…”
Section: Discussionmentioning
confidence: 99%